Plzzzzzzzzzz solve it
Attachments:
![](https://hi-static.z-dn.net/files/dd1/f56d7821c52af1b23aa829da7efea562.jpg)
Answers
Answered by
0
Answer:
mark me the brainliest
#ANSWERWITHQUALITY #BAL
Step-by-step explanation:
The qus can be re-written as,
( 3.27ˣ.27 + 27.(3³)ˣ ) / ( 3.(3³)ˣ.3² - 1/3 . 27ˣ.27 )
{taking 27ˣ common from numerator and denominator}
= [ 27ˣ(3.27+27) ] / [ 27ˣ (3.3² - 9) ]
= (3.27+27) / (3.3² - 9)
{taking 9 common from numerator and denominator}
= 9(3.3 + 3) / 9(3 - 1)
= 9+3 / 2
= 6
Similar questions